VD_FINDINFO Jug / 2013 / 296 vom 17. Juli 2013 - VD Tribunal cantonal (2013)
QUESTION PRÉJUDICIELLE, PRÉSOMPTION D'INNOCENCE | 10 CPP (CH), 130 CPP (CH), 141 CPP (CH), 158 al. 1 let. a CPP (CH), 159 CPP (CH)